Theorizing the City : The New Urban Anthropology Reader - Low, Setha M. (Book collections on Project MUSE., 1999)
Anthropological perspective are not often represented in urban studies, even though many anthropologist have been contributing actively to theory and research on urban poverty, racism, globalization, and architecture. Theorizing the City corrects this omission. Following a brief history of urban anthropology, emphasizing developments in the field during the 1990s, this volume presents twelve ethnographies of major cities in the Americas, Africa, Asia, and Europe. Five images of the city-the divided city, the contested city, the global city, the modernist city, and the postmodern city-serve as frameworks for the essays. Each section highlights current research trends such as poststructural studies of race, class and gender in the urban context; political economic studies of transnational culture; and studies of the symbolic meanings and social production of urban spaces.